The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1177/026565900001600103
|View full text |Cite
|
Sign up to set email alerts
|

Teaching pragmatics to language-learning disabled children: a treatment outcome study

Abstract: The purpose of the present investigation was to measure the effects of a treatment programme designed to improve the pragmatic language skills of children with learning disabilities. Subjects were 20 students from a laboratory primary school dedicated to addressing the needs of children with learning disabilities. The children were divided into two groups according to class. Class one consisted of six males and three females, and ranged in age from 7;6 to 9;8. Class two consisted of five males and six females,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Two studies (Bedrosian & Willis, 1987;Dollaghan & Kaston, 1986) used single-subject designs to examine within-and between-subject differences. Finally, one study (Richardson & Klecan-Aker, 2000) used a pretest-posttest group design. Table 1 summarizes the presence or absence of the six quality indicators (as noted in the last section, the seventh indicator "intention to treat" was not applicable for any of the studies) and subsequent identification of the research stage, as well as the clinical questions addressed by each study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies (Bedrosian & Willis, 1987;Dollaghan & Kaston, 1986) used single-subject designs to examine within-and between-subject differences. Finally, one study (Richardson & Klecan-Aker, 2000) used a pretest-posttest group design. Table 1 summarizes the presence or absence of the six quality indicators (as noted in the last section, the seventh indicator "intention to treat" was not applicable for any of the studies) and subsequent identification of the research stage, as well as the clinical questions addressed by each study.…”
Section: Methodsmentioning
confidence: 99%
“…The quality indicator scores for the studies ranged from 0 to 4 out of a possible 6 points for study protocol description, blinding, sampling/allocation, treatment fidelity, significance, and practical significance. Five of the eight studies provided sufficient description of the study protocol so that the treatment could be replicated (Adams et al, 2006;Dollaghan & Kaston, 1986;Klecan-Aker, 1993;Richardson & Klecan-Aker, 2000;Swanson et al, 2005); however, only two studies (Adams, 2001;Swanson et al, 2005) explicitly stated that the assessors were blind to the study conditions. None of the studies used random assignment.…”
Section: Methodology Quality and Research Stagementioning
confidence: 99%
See 1 more Smart Citation
“…Because emerging research links childhood externalizing and internalizing disorders to PLC deficits (Im-Bolter and Cohen 2007), it is both timely and important to familiarize psychologists and educators with domains of pragmatic competence and to evaluate the content and other forms of validity associated with PLC assessment instruments (Adams 2001;Adams et al 2006;Farmer and Oliver 2005;Hyter et al 2001;Penn 1999;Richardson and Klecan-Aker 2000;Weist et al 1991a, b). Fortunately, there is an extensive research and theoretical literature on many domains comprising pragmatic competence dating back to the 1970s (e.g., Freedle 1977;Halliday 1973;Hymes 1974;Russell 1979a, b, c;Schiffrin 1987;Snow and Ferguson 1977).…”
mentioning
confidence: 99%
“…Despite the efforts directed at elucidating the nature of SCP, there is little or no research evidence to support the selection of appropriate interventions for school-age children. 12 Studies of related groups tend to be small 13 but generally show effectiveness of targeted interventions. Single case studies, such as those of Timler, Olswang, and colleagues, have universally suggested that speechlanguage intervention is efficacious.…”
mentioning
confidence: 99%